Plate 8: Casting molds and cones; tongs; atmometer - Accum, Friedrich Christian (An Explanatory Dictionary of the Apparatus and Instruments Employed in the Various Operations of Philosophical and Experimental Chemistry, 1824)
Depicts casting molds and cones, cupel and crucible tongs, an anvil in figure 10, and an atmometer in figure 14.
Keywords: Chemistry; Chemical apparatus